A high-strength, high-white, transparent glaze, ceramic and preparation method thereof

By using the combination of raw materials such as potassium feldspar, doped quartz modified and modified chitosan liquid in ceramic glaze, the coordination problems of ceramic glaze in terms of transparency, whiteness, strength and anti-fouling properties are solved, and the preparation of high-strength, high-white transparent glaze is achieved, which significantly improves the product's aging resistance and solvent resistance stability.

CN119241074BActive Publication Date: 2025-03-18FUJIAN DEHUA YUQUAN TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411764271.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-18
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

Existing ceramic glazes have coordination problems in terms of transparency, whiteness, strength and anti-fouling properties, and have poor aging resistance and solvent resistance, which limits the efficiency of the product.

Method used

A combination of potassium feldspar, additives doped with quartz modified, dolomite, Dehua kaolin and modified chitosan liquid-regulated reinforcement was prepared through wet ball milling and ultrasonic treatment.

Benefits of technology

The coordinated improvement of the transparency, whiteness, strength and anti-fouling properties of the glaze are achieved, and the product's aging resistance and solvent resistance are significantly improved, which improves the product's use efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention relates to the field of ceramic technology, and in particular to a high-strength, high-whiteness, transparent glaze, ceramic and a preparation method thereof, comprising the following raw materials by weight: 25-30 parts of potassium feldspar, 10-15 parts of an additive doped with a quartz modifier, 10-15 parts of dolomite, 10-15 parts of Dehua kaolin, and 5-9 parts of a reinforcing agent adjusted by a modified chitosan solution. The glaze of the present invention uses potassium feldspar in combination with dolomite and Dehua kaolin, and the additive doped with a quartz modifier and the reinforcing agent adjusted by a modified chitosan solution are added to coordinate and cooperate with each other, so that the obtained glaze product has a coordinated improvement in transparency, whiteness, strength and anti-fouling performance, and the product has a significant effect on aging resistance and solvent resistance stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramics, and in particular to a high-strength, high-whiteness, transparent glaze, ceramics and a preparation method thereof. Background Art

[0002] Ceramics is a general term for pottery and porcelain, and is also a kind of arts and crafts in my country. Pottery and porcelain have different textures and properties. Pottery is made of clay with high viscosity and strong plasticity as the main raw material. It is opaque, has fine pores and weak water absorption, and makes a turbid sound when struck. Porcelain is made of clay, feldspar and quartz. It is translucent, non-absorbent, corrosion-resistant, and has a hard and compact body.

[0003] Existing ceramics require glazing to form a glaze layer during the production process, but the existing glazes have poor transparency and whiteness performance, and the glaze products have poor strength performance. At the same time, it is difficult for the products to achieve coordinated improvements in transparency, whiteness, strength and stain resistance. It is difficult for glaze products to achieve integrated performance effects, and the products have poor aging resistance and solvent resistance, which limits the product's use efficiency. Summary of the invention

[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a high-strength, high-whiteness, transparent glaze, ceramic and a preparation method thereof to solve the problems raised in the above background technology.

[0005] The present invention solves the technical problem by adopting the following technical solution:

[0006] The present invention provides a high-strength, high-white, transparent glaze, comprising the following raw materials in parts by weight:

[0007] 25-30 parts of potassium feldspar, 10-15 parts of an additive doped with a quartz modifier, 10-15 parts of dolomite, 10-15 parts of Dehua kaolin, and 5-9 parts of a reinforcing agent adjusted with a modified chitosan solution.

[0008] Preferably, the high-strength, high-whiteness and transparent glaze comprises the following raw materials in parts by weight:

[0009] 27.5 parts of potassium feldspar, 12.5 parts of an additive doped with a quartz modifier, 12.5 parts of dolomite, 12.5 parts of Dehua kaolin, and 7 parts of a reinforcing agent adjusted with a modified chitosan liquid.

[0010] Preferably, the preparation method of the synergist of the doped quartz modifier is:

[0011] S01: uniformly mixing sodium alginate solution, stearic acid and sodium lignin sulfonate in a weight ratio of 5-7:1:2-3 to obtain sodium alginate solution;

[0012] Firstly, the nano zinc oxide is added into a sodium silicate solution which is 3 to 5 times of the total weight of the nano zinc oxide, and then a sodium alginate solution which is 25 to 30% of the total weight of the nano zinc oxide is added and mixed and stirred sufficiently to obtain a nano zinc oxide agent;

[0013] S02: calcining the quartz powder at 210-230°C for 20-30 min, cooling it to 145-150°C at a rate of 1-3°C / min, keeping it at that temperature for 5-10 min, and finally air-cooling it to room temperature to obtain calcined quartz powder;

[0014] The hot-calcined quartz powder and the nano zinc oxide agent are stirred at a weight ratio of 3:5-6, and the stirring is completed to obtain a quartz modified body;

[0015] S03: subjecting the quartz modifier and the additive to ultrasonic treatment at a weight ratio of 7:3-4, filtering and drying after the ultrasonic treatment to obtain the additive doped with the quartz modifier.

[0016] Preferably, the mass fraction of the sodium alginate solution is 3-5%; the mass fraction of the sodium silicate solution is 2-4%;

[0017] The stirring speed of the stirring treatment is 550~750r / min, and the stirring is 20~30min; the ultrasonic power of the ultrasonic treatment is 400~500W, and the ultrasonic time is 10~15min.

[0018] Preferably, the preparation method of the additive is:

[0019] Preheating the flaky nano-alumina at 55-60° C. for 1 h to obtain preheated flaky nano-alumina; mixing 5-8 parts of the preheated flaky nano-alumina and 3-5 parts of boron nitride liquid by weight, and subjecting the mixture to ball milling at a ball milling speed of 1000 r / min for 2 h. After the ball milling is completed, the mixture is filtered and dried to obtain an additive agent;

[0020] The boron nitride liquid comprises the following raw materials in parts by weight:

[0021] 4~7 parts of boron nitride, 3~5 parts of dopamine hydrochloride solution, 2~3 parts of lanthanum oxide and 1~2 parts of barium nitrate solution.

[0022] Preferably, the mass fraction of the dopamine hydrochloride solution is 3-6%; the mass fraction of the barium nitrate solution is 2-5%.

[0023] Preferably, the preparation method of the reinforcing agent adjusted by the modified chitosan liquid is:

[0024] S11: immersing the nano-titanium dioxide into a sufficient amount of yttrium nitrate solution and stirring it sufficiently, then filtering and drying it to obtain yttrium-doped nano-titanium dioxide agent;

[0025] S12: Add 1-2 parts of silane coupling agent KH550 to 5-8 parts of chitosan solution by weight, then add 2-3 parts of silicon carbide powder and 4-7 parts of yttrium-doped nano-titanium dioxide agent, blend and stir thoroughly, filter and dry after stirring to obtain a reinforcing agent adjusted by modified chitosan solution.

[0026] Preferably, the mass fraction of the yttrium nitrate solution is 3-5%; the mass fraction of the chitosan solution is 2-4%.

[0027] The present invention also provides a method for preparing high-strength high-white ceramics, using the high-strength high-white transparent glaze, comprising the following steps:

[0028] Step 1: Preparation of ceramic body:

[0029] a. 20-25 parts of albite, 10-15 parts of clay, 10-15 parts of calcined talc, 5-8 parts of bentonite and 1-2 parts of sodium carboxymethyl cellulose were mixed and wet-milled at a speed of 1500 r / min for 2 hours to obtain a ball mill material;

[0030] b. Press the ball abrasive into a mold at a pressure of 10-15 MPa for 1 hour, and demold to obtain a ceramic body;

[0031] Step 2: Prepare high-strength, high-white, transparent glaze:

[0032] The potassium feldspar, the additive doped with the quartz modifier, dolomite, Dehua kaolin and the reinforcing agent adjusted by the modified chitosan solution are mixed and wet-milled at a ball milling speed of 1000 r / min for 3 hours to obtain a high-strength, high-white and transparent glaze;

[0033] Step 3: Glazing: Apply high-strength, high-white, transparent glaze to the ceramic body with a glaze amount of 200-220 g / m 2 , after the donation is completed, a ceramic glaze body is obtained;

[0034] Step 4: Sintering:

[0035] The ceramic glaze body is first sintered at a temperature of 550-600°C for 1 hour, then heated to 1220-1230°C at a rate of 1-3°C / min and sintered for 2 hours. After sintering, it is cooled to room temperature to obtain a high-strength and high-white ceramic.

[0036] The present invention also provides a high-strength high-white ceramic, which is prepared by the high-strength high-white ceramic preparation method.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] 1. The glaze of the present invention adopts potassium feldspar, dolomite and Dehua kaolin, and the synergist doped with quartz modifier and the reinforcing agent adjusted by modified chitosan liquid are added to coordinate and cooperate with each other, so that the transparency, whiteness, strength and anti-fouling performance of the obtained glaze product are coordinated and improved, and the product has remarkable aging resistance and solvent resistance stability effects;

[0039] 2. The additive of the doped quartz modifier uses quartz as the matrix, is calcined at 210-230°C for 20-30min, and then cooled to 145-150°C at a rate of 1-3°C / min, and kept warm for 5-10min to optimize the activity performance of quartz, and then stirred and improved by a nano zinc oxide agent. The nano zinc oxide in the nano zinc oxide agent is blended with a sodium silicate solution, and then a sodium alginate solution is obtained by co-combining a sodium alginate solution, stearic acid and sodium lignin sulfonate. The sodium alginate solution can optimize the dispersion between the raw materials, coordinate the sodium lignin sulfonate and stearic acid, and enhance the coordination effect of nano zinc oxide and sodium silicate solution. The obtained nano zinc oxide agent can better improve the quartz body, thereby optimizing the performance coordination of the product, and the performance stability of the product can be further improved by using an additive. The nano alumina in the additive is preheated, and then mixed and coordinated with boron nitride, dopamine hydrochloride solution, lanthanum oxide and barium nitrate solution. Boron nitride is used as the matrix, and dopamine hydrochloride solution, lanthanum oxide and barium nitrate solution are coordinated and coordinated with each other. The coordination effect of the additive and nano alumina is enhanced through the mutual coordination and coordination between the raw materials, and the additive of the doped quartz modifier obtained in the system further coordinates and improves the performance effect of the product, and optimizes the performance stability of the product.

[0040] 3. The reinforcing agent adjusted by the modified chitosan liquid is nano-titanium dioxide treated with yttrium nitrate solution. The nano-titanium dioxide treated with yttrium nitrate solution can better play the synergistic effect of enhancing transparency and whiteness in the system, and then the chitosan solution, silane coupling agent KH550 and silicon carbide powder are blended and coordinated. The chitosan solution has permeability, and the silane coupling agent improves the interface effect between the raw materials. The addition of silicon carbide powder coordinates the raw materials and enhances the performance stability of the system. Through the common coordination and synergy between the raw materials, the modified chitosan liquid obtained can strengthen and dope the synergist of the quartz modifier, and the synergistic effect between the product raw materials is enhanced, so that the performance of the product is further improved. DETAILED DESCRIPTION

[0041] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] A high-strength, high-white, transparent glaze in this embodiment includes the following raw materials in parts by weight:

[0043] 25-30 parts of potassium feldspar, 10-15 parts of an additive doped with a quartz modifier, 10-15 parts of dolomite, 10-15 parts of Dehua kaolin, and 5-9 parts of a reinforcing agent adjusted with a modified chitosan solution.

[0044] The preparation method of the synergist of the doped quartz modifier of this embodiment is:

[0045] S01: uniformly mixing sodium alginate solution, stearic acid and sodium lignin sulfonate in a weight ratio of 5-7:1:2-3 to obtain sodium alginate solution;

[0046] Firstly, the nano zinc oxide is added into a sodium silicate solution which is 3 to 5 times of the total weight of the nano zinc oxide, and then a sodium alginate solution which is 25 to 30% of the total weight of the nano zinc oxide is added and mixed and stirred sufficiently to obtain a nano zinc oxide agent;

[0047] S02: calcining the quartz powder at 210-230°C for 20-30 min, cooling it to 145-150°C at a rate of 1-3°C / min, keeping it at that temperature for 5-10 min, and finally air-cooling it to room temperature to obtain calcined quartz powder;

[0048] The hot-calcined quartz powder and the nano zinc oxide agent are stirred at a weight ratio of 3:5-6, and the stirring is completed to obtain a quartz modified body;

[0049] S03: subjecting the quartz modifier and the additive to ultrasonic treatment at a weight ratio of 7:3-4, filtering and drying after the ultrasonic treatment to obtain the additive doped with the quartz modifier.

[0050] The mass fraction of the sodium alginate solution in this embodiment is 3-5%; the mass fraction of the sodium silicate solution is 2-4%;

[0051] The stirring speed of the stirring treatment is 550~750r / min, and the stirring is 20~30min; the ultrasonic power of the ultrasonic treatment is 400~500W, and the ultrasonic time is 10~15min.

[0052] The preparation method of the additive agent of the present embodiment is:

[0053] Preheating the flaky nano-alumina at 55-60° C. for 1 h to obtain preheated flaky nano-alumina; mixing 5-8 parts of the preheated flaky nano-alumina and 3-5 parts of boron nitride liquid by weight, and subjecting the mixture to ball milling at a ball milling speed of 1000 r / min for 2 h. After the ball milling is completed, the mixture is filtered and dried to obtain an additive agent;

[0054] The boron nitride liquid comprises the following raw materials in parts by weight:

[0055] 4~7 parts of boron nitride, 3~5 parts of dopamine hydrochloride solution, 2~3 parts of lanthanum oxide and 1~2 parts of barium nitrate solution.

[0056] The mass fraction of the dopamine hydrochloride solution in this embodiment is 3-6%; the mass fraction of the barium nitrate solution is 2-5%.

[0057] The preparation method of the reinforcing agent adjusted by the modified chitosan liquid of this embodiment is:

[0058] S11: immersing the nano-titanium dioxide into a sufficient amount of yttrium nitrate solution and stirring it sufficiently, then filtering and drying it to obtain yttrium-doped nano-titanium dioxide agent;

[0059] S12: Add 1-2 parts of silane coupling agent KH550 to 5-8 parts of chitosan solution by weight, then add 2-3 parts of silicon carbide powder and 4-7 parts of yttrium-doped nano-titanium dioxide agent, blend and stir thoroughly, filter and dry after stirring to obtain a reinforcing agent adjusted by modified chitosan solution.

[0060] The mass fraction of the yttrium nitrate solution in this embodiment is 3-5%; the mass fraction of the chitosan solution is 2-4%.

[0061] A preparation method using high-strength high-white ceramics in this embodiment includes the following steps:

[0062] Step 1: Preparation of ceramic body:

[0063] a. 20-25 parts of albite, 10-15 parts of clay, 10-15 parts of calcined talc, 5-8 parts of bentonite and 1-2 parts of sodium carboxymethyl cellulose were mixed and wet-milled at a speed of 1500 r / min for 2 hours to obtain a ball mill material;

[0064] b. Press the ball abrasive into a mold at a pressure of 10-15 MPa for 1 hour, and demold to obtain a ceramic body;

[0065] Step 2: Prepare high-strength, high-white, transparent glaze:

[0066] The potassium feldspar, the additive doped with the quartz modifier, dolomite, Dehua kaolin and the reinforcing agent adjusted by the modified chitosan solution are mixed and wet-milled at a ball milling speed of 1000 r / min for 3 hours to obtain a high-strength, high-white and transparent glaze;

[0067] Step 3: Glazing: Apply high-strength, high-white, transparent glaze to the ceramic body with a glaze amount of 200-220 g / m 2 , after the donation is completed, a ceramic glaze body is obtained;

[0068] Step 4: Sintering:

[0069] The ceramic glaze body is first sintered at a temperature of 550-600°C for 1 hour, then heated to 1220-1230°C at a rate of 1-3°C / min and sintered for 2 hours. After sintering, it is cooled to room temperature to obtain a high-strength and high-white ceramic.

[0070] The high-strength high-white ceramic of this embodiment is prepared by the above-mentioned preparation method of the high-strength high-white ceramic.

[0071] Example 1: A high-strength, high-white, transparent glaze comprising the following raw materials in parts by weight:

[0072] 25 parts of potassium feldspar, 10 parts of an additive doped with a quartz modifier, 10 parts of dolomite, 10 parts of Dehua kaolin, and 5 parts of a reinforcing agent adjusted with a modified chitosan solution.

[0073] The preparation method of the synergist of the doped quartz modifier of this embodiment is:

[0074] S01: uniformly blending sodium alginate solution, stearic acid and sodium lignin sulfonate in a weight ratio of 5:1:2 to obtain sodium alginate solution;

[0075] The nano zinc oxide is first added into a sodium silicate solution which is 3 times the total weight of the nano zinc oxide, and then a sodium alginate solution which is 25% of the total weight of the nano zinc oxide is added and mixed and stirred sufficiently to obtain a nano zinc oxide agent;

[0076] S02: calcining the quartz powder at 210°C for 20 min, cooling it to 145°C at a rate of 1°C / min, keeping it at that temperature for 5 min, and finally air-cooling it to room temperature to obtain calcined quartz powder;

[0077] The hot-calcined quartz powder and the nano zinc oxide agent are stirred at a weight ratio of 3:5, and the stirring is completed to obtain a quartz modified body;

[0078] S03: subjecting the quartz modifier and the additive to ultrasonic treatment in a weight ratio of 7:3, filtering and drying after the ultrasonic treatment to obtain the additive doped with the quartz modifier.

[0079] The mass fraction of the sodium alginate solution in this embodiment is 3%; the mass fraction of the sodium silicate solution is 2%;

[0080] The stirring speed of the stirring treatment was 550 r / min, and the stirring was performed for 20 min. The ultrasonic power of the ultrasonic treatment was 400 W, and the ultrasonic time was 10 min.

[0081] The preparation method of the additive agent of the present embodiment is:

[0082] Preheating the flaky nano-alumina at 55° C. for 1 h to obtain preheated flaky nano-alumina; mixing 5 parts of the preheated flaky nano-alumina and 3 parts of boron nitride liquid by weight, and subjecting the mixture to ball milling at a ball milling speed of 1000 r / min for 2 h. After the ball milling is completed, the mixture is filtered and dried to obtain an additive agent;

[0083] The boron nitride liquid comprises the following raw materials in parts by weight:

[0084] 4 parts of boron nitride, 3 parts of dopamine hydrochloride solution, 2 parts of lanthanum oxide and 1 part of barium nitrate solution.

[0085] The mass fraction of the dopamine hydrochloride solution in this embodiment is 3%; the mass fraction of the barium nitrate solution is 2%.

[0086] The preparation method of the reinforcing agent adjusted by the modified chitosan liquid of this embodiment is:

[0087] S11: immersing the nano-titanium dioxide into a sufficient amount of yttrium nitrate solution and stirring it sufficiently, then filtering and drying it to obtain yttrium-doped nano-titanium dioxide agent;

[0088] S12: Add 1 part of silane coupling agent KH550 to 5 parts of chitosan solution by weight, then add 2 parts of silicon carbide powder and 4 parts of yttrium-doped nano-titanium dioxide agent, blend and stir thoroughly, filter and dry after stirring to obtain a reinforcing agent adjusted by modified chitosan solution.

[0089] The mass fraction of the yttrium nitrate solution in this embodiment is 3%; the mass fraction of the chitosan solution is 2%.

[0090] A preparation method using high-strength high-white ceramics in this embodiment includes the following steps:

[0091] Step 1: Preparation of ceramic body:

[0092] a. 20 parts of albite, 10 parts of clay, 10 parts of calcined talc, 5 parts of bentonite and 1 part of sodium carboxymethyl cellulose were mixed and wet-milled at a speed of 1500 r / min for 2 h to obtain a ball mill material;

[0093] b. Press the ball abrasive into a mold at a pressure of 10 MPa for 1 h, and demold to obtain a ceramic body;

[0094] Step 2: Prepare high-strength, high-white, transparent glaze:

[0095] The potassium feldspar, the additive doped with the quartz modifier, dolomite, Dehua kaolin and the reinforcing agent adjusted by the modified chitosan solution are mixed and wet-milled at a ball milling speed of 1000 r / min for 3 hours to obtain a high-strength, high-white and transparent glaze;

[0096] Step 3: Glazing: Apply high-strength, high-white, transparent glaze to the ceramic body with a glaze amount of 200g / m 2 , after the donation is completed, a ceramic glaze body is obtained;

[0097] Step 4: Sintering:

[0098] The ceramic glaze body is first sintered at 550°C for 1 hour, then heated to 1220°C at a rate of 1°C / min and sintered for 2 hours. After sintering, it is cooled to room temperature to obtain a high-strength and high-white ceramic.

[0099] The high-strength high-white ceramic of this embodiment is prepared by the above-mentioned preparation method of the high-strength high-white ceramic.

[0100] Example 2: A high-strength, high-white, transparent glaze comprising the following raw materials in parts by weight:

[0101] 30 parts of potassium feldspar, 15 parts of an additive doped with a quartz modifier, 15 parts of dolomite, 15 parts of Dehua kaolin, and 9 parts of a reinforcing agent adjusted with a modified chitosan solution.

[0102] The preparation method of the synergist of the doped quartz modifier of this embodiment is:

[0103] S01: uniformly mixing sodium alginate solution, stearic acid and sodium lignin sulfonate in a weight ratio of 7:1:3 to obtain sodium alginate solution;

[0104] The nano zinc oxide is first added into a sodium silicate solution which is 5 times the total weight of the nano zinc oxide, and then a sodium alginate solution which is 30% of the total weight of the nano zinc oxide is added and mixed and stirred sufficiently to obtain a nano zinc oxide agent;

[0105] S02: calcining the quartz powder at 230°C for 30 min, cooling it to 150°C at a rate of 3°C / min, keeping it at that temperature for 10 min, and finally air-cooling it to room temperature to obtain calcined quartz powder;

[0106] The hot-calcined quartz powder and the nano zinc oxide agent are stirred at a weight ratio of 3:6, and after the stirring is completed, a quartz modified body is obtained;

[0107] S03: subjecting the quartz modifier and the additive to ultrasonic treatment in a weight ratio of 7:4, filtering and drying after the ultrasonic treatment to obtain the additive doped with the quartz modifier.

[0108] The mass fraction of the sodium alginate solution in this embodiment is 5%; the mass fraction of the sodium silicate solution is 4%;

[0109] The stirring speed of the stirring treatment was 750 r / min, and the stirring was performed for 30 min. The ultrasonic power of the ultrasonic treatment was 500 W, and the ultrasonic time was 15 min.

[0110] The preparation method of the additive agent of the present embodiment is:

[0111] Preheating the flaky nano-alumina at 60° C. for 1 h to obtain preheated flaky nano-alumina; mixing 8 parts of the preheated flaky nano-alumina and 5 parts of boron nitride liquid by weight, and subjecting the mixture to ball milling at a speed of 1000 r / min for 2 h. After the ball milling is completed, the mixture is filtered and dried to obtain an additive agent;

[0112] The boron nitride liquid comprises the following raw materials in parts by weight:

[0113] 7 parts of boron nitride, 5 parts of dopamine hydrochloride solution, 3 parts of lanthanum oxide and 2 parts of barium nitrate solution.

[0114] The mass fraction of the dopamine hydrochloride solution in this embodiment is 6%; the mass fraction of the barium nitrate solution is 5%.

[0115] The preparation method of the reinforcing agent adjusted by the modified chitosan liquid of this embodiment is:

[0116] S11: immersing the nano-titanium dioxide into a sufficient amount of yttrium nitrate solution and stirring it sufficiently, then filtering and drying it to obtain yttrium-doped nano-titanium dioxide agent;

[0117] S12: Add 2 parts of silane coupling agent KH550 to 8 parts of chitosan solution by weight, then add 3 parts of silicon carbide powder and 7 parts of yttrium-doped nano-titanium dioxide agent, blend and stir thoroughly, filter and dry after stirring to obtain a reinforcing agent adjusted by modified chitosan solution.

[0118] The mass fraction of the yttrium nitrate solution in this embodiment is 5%; the mass fraction of the chitosan solution is 4%.

[0119] A preparation method using high-strength high-white ceramics in this embodiment includes the following steps:

[0120] Step 1: Preparation of ceramic body:

[0121] a. 25 parts of albite, 15 parts of clay, 15 parts of calcined talc, 8 parts of bentonite and 2 parts of sodium carboxymethyl cellulose were mixed and wet-milled at a speed of 1500 r / min for 2 h to obtain a ball mill material;

[0122] b. Press the ball abrasive into a mold at a pressure of 15 MPa for 1 h, and demold to obtain a ceramic body;

[0123] Step 2: Prepare high-strength, high-white, transparent glaze:

[0124] The potassium feldspar, the additive doped with the quartz modifier, dolomite, Dehua kaolin and the reinforcing agent adjusted by the modified chitosan solution are mixed and wet-milled at a ball milling speed of 1000 r / min for 3 hours to obtain a high-strength, high-white and transparent glaze;

[0125] Step 3: Glazing: Apply high-strength, high-white, transparent glaze to the ceramic body with a glaze amount of 220g / m 2 , after the donation is completed, a ceramic glaze body is obtained;

[0126] Step 4: Sintering:

[0127] The ceramic glaze body is first sintered at 600°C for 1 hour, then heated to 1230°C at a rate of 3°C / min and sintered for 2 hours. After sintering, it is cooled to room temperature to obtain a high-strength and high-white ceramic.

[0128] The high-strength high-white ceramic of this embodiment is prepared by the above-mentioned preparation method of the high-strength high-white ceramic.

[0129] Embodiment 3: A high-strength, high-white, transparent glaze comprising the following raw materials in parts by weight:

[0130] 27.5 parts of potassium feldspar, 12.5 parts of an additive doped with a quartz modifier, 12.5 parts of dolomite, 12.5 parts of Dehua kaolin, and 7 parts of a reinforcing agent adjusted with a modified chitosan liquid.

[0131] The preparation method of the synergist of the doped quartz modifier of this embodiment is:

[0132] S01: mixing sodium alginate solution, stearic acid and sodium lignin sulfonate in a weight ratio of 6:1:2.5 to obtain sodium alginate solution;

[0133] The nano zinc oxide is first added into a sodium silicate solution which is 4 times the total weight of the nano zinc oxide, and then a sodium alginate solution which is 27.5% of the total weight of the nano zinc oxide is added and mixed and stirred sufficiently to obtain a nano zinc oxide agent;

[0134] S02: The quartz powder is first calcined at 220°C for 25 min, then cooled to 147°C at a rate of 2°C / min, kept at that temperature for 7.5 min, and finally air-cooled to room temperature to obtain calcined quartz powder;

[0135] The hot-calcined quartz powder and the nano zinc oxide agent are stirred at a weight ratio of 3:5.5, and the stirring is completed to obtain a quartz modified body;

[0136] S03: subjecting the quartz modifier and the additive to ultrasonic treatment in a weight ratio of 7:3.5, filtering and drying after the ultrasonic treatment to obtain the additive doped with the quartz modifier.

[0137] The mass fraction of the sodium alginate solution in this embodiment is 4%; the mass fraction of the sodium silicate solution is 3%;

[0138] The stirring speed of the stirring treatment was 600 r / min, and the stirring was performed for 25 min. The ultrasonic power of the ultrasonic treatment was 450 W, and the ultrasonic time was 12.5 min.

[0139] The preparation method of the additive agent of the present embodiment is:

[0140] Preheating the flaky nano-alumina at 57° C. for 1 h to obtain preheated flaky nano-alumina; mixing 6.5 parts of the preheated flaky nano-alumina and 4 parts of boron nitride liquid by weight, and subjecting the mixture to ball milling at a ball milling speed of 1000 r / min for 2 h; after the ball milling is completed, filtering and drying are performed to obtain an additive agent;

[0141] The boron nitride liquid comprises the following raw materials in parts by weight:

[0142] 5.5 parts of boron nitride, 4 parts of dopamine hydrochloride solution, 2.5 parts of lanthanum oxide and 1.5 parts of barium nitrate solution.

[0143] The mass fraction of the dopamine hydrochloride solution in this embodiment is 4.5%; the mass fraction of the barium nitrate solution is 3.5%.

[0144] The preparation method of the reinforcing agent adjusted by the modified chitosan liquid of this embodiment is:

[0145] S11: immersing the nano-titanium dioxide into a sufficient amount of yttrium nitrate solution and stirring it sufficiently, then filtering and drying it to obtain yttrium-doped nano-titanium dioxide agent;

[0146] S12: Add 1.5 parts of silane coupling agent KH550 to 6.5 parts of chitosan solution by weight, then add 2.5 parts of silicon carbide powder and 5.5 parts of yttrium-doped nano-titanium dioxide agent, blend and stir thoroughly, filter and dry after stirring to obtain a reinforcing agent adjusted by modified chitosan solution.

[0147] The mass fraction of the yttrium nitrate solution in this embodiment is 4%; the mass fraction of the chitosan solution is 3%.

[0148] A preparation method using high-strength high-white ceramics in this embodiment includes the following steps:

[0149] Step 1: Preparation of ceramic body:

[0150] a. 22.5 parts of albite, 12.5 parts of clay, 12.5 parts of calcined talc, 6.5 parts of bentonite and 1.5 parts of sodium carboxymethyl cellulose were mixed and wet-milled at a speed of 1500 r / min for 2 h to obtain a ball mill material;

[0151] b. Press the ball abrasive into a mold at a pressure of 12.5 MPa for 1 h, and demold to obtain a ceramic body;

[0152] Step 2: Prepare high-strength, high-white, transparent glaze:

[0153] The potassium feldspar, the additive doped with the quartz modifier, dolomite, Dehua kaolin and the reinforcing agent adjusted by the modified chitosan solution are mixed and wet-milled at a ball milling speed of 1000 r / min for 3 hours to obtain a high-strength, high-white and transparent glaze;

[0154] Step 3: Glazing: Apply high-strength, high-white, transparent glaze to the ceramic body with a glaze amount of 210g / m 2 , after the donation is completed, a ceramic glaze body is obtained;

[0155] Step 4: Sintering:

[0156] The ceramic glaze body is first sintered at 570°C for 1 hour, then heated to 1225°C at a rate of 2°C / min and sintered for 2 hours. After sintering, it is cooled to room temperature to obtain a high-strength and high-white ceramic.

[0157] The high-strength high-white ceramic of this embodiment is prepared by the above-mentioned preparation method of the high-strength high-white ceramic.

[0158] Comparative Example 1:

[0159] The difference from Example 3 is that no synergist for doping the quartz modifier is added.

[0160] Comparative Example 2:

[0161] The difference from Example 3 is that no quartz modifier is added in the preparation of the additive doped with quartz modifier.

[0162] Comparative Example 3:

[0163] The difference from Example 3 is that the quartz powder that is thermally calcined in the preparation of the quartz modifier is replaced by quartz powder raw material.

[0164] Comparative Example 4:

[0165] The difference from Example 3 is that nano zinc oxide treatment is not used in the preparation of the additive for the doped quartz modifier.

[0166] Comparative Example 5:

[0167] The difference from Example 3 is that no sodium alginate solution is added to the nano zinc oxide agent.

[0168] Comparative Example 6:

[0169] The difference from Example 3 is that no additive treatment is added during the preparation of the additive of the doped quartz modifier.

[0170] Comparative Example 7:

[0171] The difference from Example 3 is that no reinforcing agent adjusted by modified chitosan liquid is added.

[0172] Comparative Example 8:

[0173] The difference from Example 3 is that no yttrium-doped nano-titanium dioxide agent is added to the reinforcing agent adjusted by the modified chitosan solution.

[0174] Comparative Example 9:

[0175] The difference from Example 3 is that the yttrium-doped nano-titanium dioxide agent is replaced by nano-titanium dioxide.

[0176] Comparative Example 10:

[0177] The difference from Example 3 is that silicon carbide powder and silane coupling agent KH550 are not added to the reinforcing agent adjusted by the modified chitosan liquid.

[0178] The ceramic products of Examples 1 to 3 and Comparative Examples 1 to 10 were subjected to conventional performance tests of transparency, whiteness, strength and anti-fouling. The test results are shown in Table 1.

[0179] Table 1 Conventional performance test results of ceramic products of Examples 1 to 3 and Comparative Examples 1 to 10:

[0180]

[0181] The ceramic products of Examples 1 to 3 and Comparative Examples 1 to 10 were subjected to 100 h of UV irradiation aging treatment at an irradiation intensity of 100 mW / cm 2 , test the aging resistance, and immerse the product in acetone solvent for 48 hours to test the solvent resistance. The test results are shown in Table 2.

[0182] Table 2 Test results of aging resistance and solvent resistance of ceramic products of Examples 1 to 3 and Comparative Examples 1 to 10:

[0183]

[0184] From comparative examples 1-10 and examples 1-3 as well as the aging resistance and solvent resistance tests, it can be seen that the product of example 3 has excellent transparency, whiteness, strength and anti-fouling properties, and the product performance can be improved in a coordinated manner, and the product aging resistance and solvent resistance stability effects are remarkable;

[0185] The present invention does not add a synergist doped with a quartz modifier or a reinforcing agent adjusted with a modified chitosan solution, and the performance of the product deteriorates significantly. The two are used in combination to achieve synergistic effects, and the product performance effect is significant.

[0186] In the preparation of the additive of the doped quartz modifier, the quartz modifier is not added, the quartz powder calcined in the preparation of the quartz modifier is replaced by the quartz powder raw material, the nano zinc oxide agent is not used in the preparation of the additive of the doped quartz modifier, the sodium alginate solution is not added to the nano zinc oxide agent, and the additive of the doped quartz modifier is not added. The performance of the product has a tendency to deteriorate, especially without the addition of the additive. The performance of the product deteriorates significantly. At the same time, the quartz modifier obtained by the method of the present invention is combined with the nano zinc oxide agent and the additive. The performance effect of the product is the most significant, and the use of other methods instead is not as obvious as the effect of the present invention;

[0187] The performance of the products tended to deteriorate when the yttrium-doped nano-titanium dioxide agent was not added to the reinforcing agent adjusted by the modified chitosan liquid, the yttrium-doped nano-titanium dioxide agent was replaced by nano-titanium dioxide, and the silicon carbide powder and the silane coupling agent KH550 were not added to the reinforcing agent adjusted by the modified chitosan liquid. The performance effect of the products was the most significant when the yttrium-doped nano-titanium dioxide agent obtained by the specific method of the present invention was combined with silicon carbide powder and the silane coupling agent KH550, and the reinforcing agent adjusted by the modified chitosan liquid obtained by the specific method was obtained.

[0188] At the same time, the inventors of the present application also found that without adding an additive, the product performance deteriorated significantly. Based on this, the present invention further explored the influence of the preparation of an additive on the product performance.

[0189] Experimental Example 1:

[0190] The only difference from Example 3 is that boron nitride liquid treatment is not used.

[0191] Experimental Example 2:

[0192] The only difference from Example 3 is that no boron nitride is added to the boron nitride liquid.

[0193] Experimental Example 3:

[0194] The only difference from Example 3 is that lanthanum oxide is not added to the boron nitride liquid.

[0195] Experimental Example 4:

[0196] The only difference from Example 3 is that no barium nitrate solution is added to the boron nitride solution.

[0197] Experimental Example 5:

[0198] The only difference from Example 3 is that no dopamine hydrochloride solution is added to the boron nitride solution.

[0199] Experimental Example 6:

[0200] The only difference from Example 3 is that no preheated flaky nano-alumina is added.

[0201] The ceramic products of Experimental Examples 1 to 6 were subjected to UV irradiation aging treatment for 100 h at an irradiation intensity of 100 mW / cm 2 , test the aging resistance, and immerse the product in acetone solvent for 48 hours to test the solvent resistance. The test results are shown in Table 3.

[0202] Table 3 Test results of aging resistance and solvent resistance of ceramic products of Experimental Examples 1 to 6:

[0203]

[0204] It can be seen from Experimental Examples 1-6 that the performance of the product changes when boron nitride liquid treatment is not used in the preparation of the additive-effective agent. Among the factors in the preparation of the additive-effective agent, the performance deterioration is the most obvious, followed by the fact that no preheated flaky nano-alumina is added. At the same time, no boron nitride is added to the boron nitride liquid, no lanthanum oxide is added to the boron nitride liquid, no barium nitrate solution is added to the boron nitride liquid, and no dopamine hydrochloride solution is added to the boron nitride liquid. The performance of the product has a tendency to deteriorate. The composition of the boron nitride liquid is specific. At the same time, the additive-effective agent obtained by using a specific boron nitride liquid and preheated flaky nano-alumina has a unique product preparation process. Only the additive-effective agent obtained by the specific method of the present invention has the most significant product performance effect. Using other methods instead is not as significant as the effect of the present invention.

[0205] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0206] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A high-strength, high-white, transparent glaze, characterized in that: It includes the following raw materials in parts by weight: 25-30 parts of potassium feldspar, 10-15 parts of additive doped with quartz modifier, 10-15 parts of dolomite, 10-15 parts of Dehua kaolin, 5-9 parts of reinforcing agent adjusted by modified chitosan liquid; The preparation method of the synergist of the doped quartz modifier is as follows: S01: uniformly mixing sodium alginate solution, stearic acid and sodium lignin sulfonate in a weight ratio of 5-7:1:2-3 to obtain sodium alginate solution; Firstly, the nano zinc oxide is added into a sodium silicate solution which is 3 to 5 times of the total weight of the nano zinc oxide, and then a sodium alginate solution which is 25 to 30% of the total weight of the nano zinc oxide is added and mixed and stirred sufficiently to obtain a nano zinc oxide agent; S02: calcining the quartz powder at 210-230°C for 20-30 min, cooling it to 145-150°C at a rate of 1-3°C / min, keeping it at that temperature for 5-10 min, and finally air-cooling it to room temperature to obtain calcined quartz powder; The hot-calcined quartz powder and the nano zinc oxide agent are stirred at a weight ratio of 3:5-6, and the stirring is completed to obtain a quartz modified body; S03: subjecting the quartz modifier and the additive to ultrasonic treatment at a weight ratio of 7:3-4, filtering and drying after the ultrasonic treatment to obtain the additive doped with the quartz modifier; The preparation method of the additive is as follows: Preheating the flaky nano-alumina at 55-60°C for 1 hour to obtain preheated flaky nano-alumina; mixing 5-8 parts of the preheated flaky nano-alumina and 3-5 parts of boron nitride liquid by weight, and subjecting the mixture to ball milling at a ball milling speed of 1000 r / min for 2 hours; after the ball milling is completed, filtering and drying are performed to obtain an additive agent; The boron nitride liquid comprises the following raw materials in parts by weight: 4-7 parts of boron nitride, 3-5 parts of dopamine hydrochloride solution, 2-3 parts of lanthanum oxide and 1-2 parts of barium nitrate solution; The preparation method of the reinforcing agent adjusted by the modified chitosan liquid is: S11: immersing the nano-titanium dioxide into a sufficient amount of yttrium nitrate solution and stirring it sufficiently, then filtering and drying it to obtain yttrium-doped nano-titanium dioxide agent; S12: Add 1-2 parts of silane coupling agent KH550 to 5-8 parts of chitosan solution by weight, then add 2-3 parts of silicon carbide powder and 4-7 parts of yttrium-doped nano-titanium dioxide agent, blend and stir thoroughly, filter and dry after stirring to obtain a reinforcing agent adjusted by modified chitosan solution.

2. The high-strength, high-whiteness, transparent glaze according to claim 1, characterized in that: The high-strength, high-white, transparent glaze comprises the following raw materials in parts by weight: 27.5 parts of potassium feldspar, 12.5 parts of an additive doped with a quartz modifier, 12.5 parts of dolomite, 12.5 parts of Dehua kaolin, and 7 parts of a reinforcing agent adjusted with a modified chitosan liquid.

3. The high-strength, high-white, transparent glaze according to claim 1, characterized in that: The mass fraction of the sodium alginate solution is 3-5%; the mass fraction of the sodium silicate solution is 2-4%; The stirring speed of the stirring treatment is 550~750r / min, and the stirring is 20~30min; the ultrasonic power of the ultrasonic treatment is 400~500W, and the ultrasonic time is 10~15min.

4. The high-strength, high-white, transparent glaze according to claim 1, characterized in that: The mass fraction of the dopamine hydrochloride solution is 3-6%; the mass fraction of the barium nitrate solution is 2-5%.

5. The high-strength, high-white, transparent glaze according to claim 1, characterized in that: The mass fraction of the yttrium nitrate solution is 3-5%; the mass fraction of the chitosan solution is 2-4%.

6. A method for preparing high-strength high-white ceramics, using the high-strength high-white transparent glaze according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step 1: Preparation of ceramic body: a. 20-25 parts of albite, 10-15 parts of clay, 10-15 parts of calcined talc, 5-8 parts of bentonite and 1-2 parts of sodium carboxymethyl cellulose were mixed and wet-milled at a speed of 1500 r / min for 2 hours to obtain a ball mill material; b. Press the ball abrasive into a mold at a pressure of 10-15 MPa for 1 hour, and demold to obtain a ceramic body; Step 2: Prepare high-strength, high-white, transparent glaze: The potassium feldspar, the additive doped with the quartz modifier, dolomite, Dehua kaolin and the reinforcing agent adjusted by the modified chitosan solution are mixed and wet-milled at a ball milling speed of 1000 r / min for 3 hours to obtain a high-strength, high-white and transparent glaze; Step 3: Glazing: Apply high-strength, high-white, transparent glaze to the ceramic body with a glaze amount of 200-220 g / m 2 , after the donation is completed, a ceramic glaze body is obtained; Step 4: Sintering: The ceramic glaze body is first sintered at a temperature of 550-600°C for 1 hour, then heated to 1220-1230°C at a rate of 1-3°C / min and sintered for 2 hours. After sintering, it is cooled to room temperature to obtain a high-strength and high-white ceramic.

7. A high-strength high-white ceramic prepared by the preparation method of the high-strength high-white ceramic according to claim 6.

Citation Information

Patent Citations

  • Underglaze blue glaze water, underglaze blue ceramic and preparation method of underglaze blue ceramic

    CN119038954A